2006
DOI: 10.1186/1472-6920-6-12
|View full text |Cite
|
Sign up to set email alerts
|

Can standardized patients replace physicians as OSCE examiners?

Abstract: BackgroundTo reduce inter-rater variability in evaluations and the demand on physician time, standardized patients (SP) are being used as examiners in OSCEs. There is concern that SP have insufficient training to provide valid evaluation of student competence and/or provide feedback on clinical skills. It is also unknown if SP ratings predict student competence in other areas. The objectives of this study were: to examine student attitudes towards SP examiners; to compare SP and physician evaluations of compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 11 publications
7
41
0
2
Order By: Relevance
“…22,23 Although a larger number of stations has been used to increase the reliability of OSCE in a highstake setting (such as The Pharmacy Examining Board of Canada's Qualifying Examination), 14 a small OSCE station number, in conjunction with the written exam, can serve as a reliable, valid and economically feasible global assessment method of student performance. 18,20 Although we did not conduct any interrater reliability testing, the similarity in the exam scores indicated that the interrater and interpatient variability didn't affect reliability of the exam.…”
Section: The Interpatient and Interrater Variabilitymentioning
confidence: 99%
“…22,23 Although a larger number of stations has been used to increase the reliability of OSCE in a highstake setting (such as The Pharmacy Examining Board of Canada's Qualifying Examination), 14 a small OSCE station number, in conjunction with the written exam, can serve as a reliable, valid and economically feasible global assessment method of student performance. 18,20 Although we did not conduct any interrater reliability testing, the similarity in the exam scores indicated that the interrater and interpatient variability didn't affect reliability of the exam.…”
Section: The Interpatient and Interrater Variabilitymentioning
confidence: 99%
“…Diferentes estudios en los que se evalúa la competencia clínica se han realizado en poblaciones de médicos residentes en formación 20,21 , o de estudiantes de medicina 22,23 , y si bien es cierto que también se dispone de datos publicados en poblaciones de médicos en ejercicio 10,17 , son poblaciones menores y normalmente referidos a una CCAA concreta. La mayor experiencia en la evaluación de la competencia clíni-ca de profesionales en ejercicio en España corresponde al Institut d'Estudis de la Salut (IES), que trabaja en la metodología ECOE en España desde hace más de 20 años, y que, por tanto, dispone de la mejor casuística en nuestro país 5 .…”
Section: Discussionunclassified
“…Weekly quiz were put for them to keep connect with the course tutor. OSCE is the standard system for evaluation to all medical students in clinical phase education [9]. Questionnaire was used to monitor student satisfaction and their recommendations to be taken in consideration for future groups.…”
Section: Discussionmentioning
confidence: 99%